2007
DOI: 10.1104/pp.107.104752
|View full text |Cite
|
Sign up to set email alerts
|

Oxo-Phytodienoic Acid-Containing Galactolipids in Arabidopsis: Jasmonate Signaling Dependence

Abstract: The jasmonate family of phytohormones, as represented by 12-oxo-phytodienoic acid (OPDA), dinor-phytodienoic acid (dn-OPDA), and jasmonic acid in Arabidopsis (Arabidopsis thaliana), has been implicated in a vast array of different developmental processes and stress responses. Recent reports indicate that OPDA and dn-OPDA occur not only as free acids in Arabidopsis, but also as esters with complex lipids, so-called arabidopsides. Recently, we showed that recognition of the two bacterial effector proteins AvrRpm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(167 citation statements)
references
References 63 publications
(90 reference statements)
7
157
1
2
Order By: Relevance
“…The upregulation of some of these early JA biosynthesis genes in developing pxa1-1 seeds suggests that there might be an increased flux of precursors including OPDA through the JA biosynthesis pathway. A large amount of OPDA and dnOPDA is found esterified in chloroplast galactolipids in Arabidopsis (Stelmach et al, 2001;Hisamatsu et al, 2003Hisamatsu et al, , 2005Andersson et al, 2006;Buseman et al, 2006;Nakajyo et al, 2006;Bö ttcher and Weiler, 2007;Kourtchenko et al, 2007). Stelmach et al (2001) showed that OPDA esterified at the sn1 position in galactolipids could be released by sn1-specific lipases.…”
Section: Accumulation Of Oxylipins In Cts/pxa1 Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of some of these early JA biosynthesis genes in developing pxa1-1 seeds suggests that there might be an increased flux of precursors including OPDA through the JA biosynthesis pathway. A large amount of OPDA and dnOPDA is found esterified in chloroplast galactolipids in Arabidopsis (Stelmach et al, 2001;Hisamatsu et al, 2003Hisamatsu et al, , 2005Andersson et al, 2006;Buseman et al, 2006;Nakajyo et al, 2006;Bö ttcher and Weiler, 2007;Kourtchenko et al, 2007). Stelmach et al (2001) showed that OPDA esterified at the sn1 position in galactolipids could be released by sn1-specific lipases.…”
Section: Accumulation Of Oxylipins In Cts/pxa1 Seedsmentioning
confidence: 99%
“…Dinor-oxo-phytodienoic acid (dnOPDA) is a 16-carbon homolog of OPDA that is synthesized from 16:3 fatty acid via a parallel hexadecanoid pathway (Weber et al, 1997;Acosta and Farmer, 2010). OPDA and dnOPDA containing galactolipids have been found in Arabidopsis, indicating that these compounds also exist in an esterified form (Stelmach et al, 2001;Hisamatsu et al, 2003Hisamatsu et al, , 2005Andersson et al, 2006;Buseman et al, 2006;Nakajyo et al, 2006;Bö ttcher and Weiler, 2007;Kourtchenko et al, 2007;Glauser et al, 2008). OPDA is transported from the plastid to the peroxisome, where CTS has been shown to be involved in its transport into the peroxisome (Theodoulou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The free hexadecatrienoic acid (16:3) liberated by a phospholipase A2 from the sn-2 position of MGDG or DGDG can also become substrate for JA biosynthesis to form dn-OPDA (Figure 3). Alternatively, 13-LOX may oxygenate 18:3 and 16:3 esterified in galactolipids (Buseman et al, 2006;Kourtchenko et al, 2007). The resulting hydroperoxy galactolipids may then be substrates for AOS and AOC, yielding arabidopsides, which belong to galactolipid species containing esterified OPDA and dnOPDA in plastidic membranes.…”
Section: Phosholipase a (Pla)mentioning
confidence: 99%
“…16,17,45 After disruption of cellular integrity arabidopsides are formed from esterified fatty acids indicating that LOX, AOS and AOC act on membrane-bound substrates. 46 Arabidopsides were discussed to function as a storage pool of OPDA, as active agents against bacterial and fungal pathogens 47 as well as senescence-promoting compounds. 48 There is not mechanistic explanation for OPDA perception, which means existence of a putative OPDA receptor.…”
mentioning
confidence: 99%